Corporate Social Responsibility of the Hospitality Industry in Realizing Sustainable Tourism Development - Willya Achmad; Yulianah Yulianah (Institute of Computer Science (IOCS), 2022)
Economic growth fueled by tourism encourages the government to support public policies aimed at regional development; as a result, a practical approach must be included from a perspective based on three responsibilities, covering the economic, social, and environmental fields, to be effective economic growth fueled by tourism. This article contains conceptual elements supported by up-to-date information from specialized and high-level scientific databases. It explains the relationship between Corporate Social Responsibility in the hospitality industry, the benefits and innovation of good practice, and the achievement of long-term goals. The overall goal is to consolidate the most remarkable industry experiences to be utilized internationally with a strategic approach and without regard to the size of the enterprise involved. An exploratory qualitative technique is used in this study and descriptive analysis and data presentation.